Difference not deficit: The Teach-Assess-Teach dialectical pedagogical model for transformative education - Hardman, J. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
Abstract only This quote from Vygotsky indicates how education functions as a mechanism for political ends. This is perhaps most evident in a country such as South Africa where the apartheid regime systematically undereducated and marginalised black[1] students in schools in a bid to produce workers for the, amongst other things, mines. A multicultural society, South Africa has 11 nationally recognised languages, which, together with its history of segregation lends itself to the use of cultural historical theory to understand the complexities in this society, especially in relation to education. Seeking to overcome the segregated education of the past, South Africa embarked in the late 1990s on a move towards inclusive education, where neurodiverse[2] and neurotypical children would be primarily included in the same classrooms. It is in the notion of inclusion, then, that Vygotsky's understanding of defectology as entailing a dialectical approach to development, that sees development as resulting from how an individual experiences and is experienced in social context provides a useful lens for investigating pedagogy. In this paper a model of pedagogy for inclusive education is outlined with reference to a single case study of students doing their Honour degrees at a university in Cape Town. Findings from 52 students indicate that the model of pedagogy outlined in this paper not only facilitates more interaction in a lecture hall but is also useful for helping students to access high level concepts. [1] The use of racial categories is recognised as problematic in the 21st century. However, these words continue to be used in the South African context and have some ability to focus social justice interventions. [2] I use the term neurodiverse here to distinguish children who do not follow the evolutionary norm that neurotypical students do. Приведенный фрагмент текста объясняет, как образование может использоваться для достижения политических целей. Особенно это заметно в Южной Африке, где во времена апартеида чернокожие[1] студенты были недообучены и маргинализированы, чтобы подготовить их к тяжелой работе, прежде всего работе в шахтах. Южно-Африканская Республика представляет собой многонациональное общество, в котором 11 официальных языков и богатая история их разделения, что делает важным использование культурно-исторической теории для понимания проблем системы образования. После окончания апартеида в конце 1990-х годов Южная Африка начала переход к инклюзивному образованию - т. е. к тому, чтобы нейроразнообразные[2] и нейротипичные дети учились вместе в одних классах. В этом контексте идеи Л.С. Выготского о дефектологии помогают понять развитие человека как результат его взаимодействия с обществом и окружающей средой. Это важно для разработки методов обучения, которые учитывают социальный опыт каждого человека. В статье предлагается модель педагогики для инклюзивного образования на основе исследования студентов магистратуры в университете Кейптауна. Анализ данных 52 студентов показывает, что эта модель помогает сделать лекции более интерактивными и способствует лучшему усвоению сложных понятий. [1] Использование расовых категорий признается проблематичным в XXI веке. Тем не менее, в южноафриканском контексте эти термины по-прежнему применяются и могут способствовать акцентированию внимания на вопросах социальной справедливости. [2] Мною использован термин «нейроразнообразные» чтобы отличить детей, которые не соответствуют эволюционной норме, присущей нейротипичным студентам.